Development of Worksheets for High School Biology Students Based On Critical Thinking Skills on the Archaebacteria and Eubacteria - Datin Maghfirotul Nadhira; Muhammad Zaini; Hardiansyah Hardiansyah (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2020)
The learning process in the 2013 curriculum has accommodated learning models that demand and facilitate Critical Thinking skills, but the role of teaching materials namely the Student Worksheet (LKPD) used in the learning process is still lacking in facilitating Critical Thinking skills students. With the existence of quality LKPD, it is expected that learning will be able to achieve the 2013 curriculum objectives. This type of research is a research development with the stages of expert review, one to one evaluation, and small group evaluation. The subjects of the small group evaluation were six students of class XI MIA 2 in SMAN 9 Banjarmasin. The results of the study show the effectiveness of expectations based on the assessment of the critical thinking skills of the participants enjoyed in working on the LKPD which has very good categories (including interpretation, analysis, evaluation, and self-regulation) and good categories (including inference and explanation). Interpersonal (collaborating) and intrapersonal (meticulous) skills of students have excellent categories.AbstrakProses pembelajaran pada kurikulum 2013 sudah mengakomodir model pembelajaran yang menuntut dan memfasilitasi keterampilan Berpikir Kritis (KBK), tetapi peran bahan ajar yakni Lembar Kerja Peserta Didik (LKPD) yang digunakan pada proses pembelajaran masih kurang dalam memfasilitasi KBK peserta didik. Adanya LKPD yang berkualitas diharapkan pembelajaran mampu mencapai tujuan kurikulum 2013. Penelitian ini bertujuan untuk mendeskripsikan keefektifan LKPD pada konsep Archaebacteria dan Eubacteria berbasis KBK. Jenis penelitian ini merupakan penelitian pengembangan dengan tahapan uji pakar, uji perorangan dan uji kelompok kecil. Subjek uji pakar adalah dua orang dosen Pendidikan Biologi. Subjek uji kelompok kecil adalah enam orang peserta didik kelas XI MIA 2 SMAN 9 Banjarmasin. Hasil penelitiann menunjukan keefektifan harapan berdasarkan dari penilaian keterampilan berpikir kritis peserta didik dalam mengerjakan LKPD yang memiliki kategori sangat baik (meliputi interpretasi, analisis, evaluasi dan pengaturan diri) dan kategori baik (meliputi inferensi dan eksplanasi). Keterampilan interpersonal (bekerjasama) dan keterampilan intrapersonal (teliti) peserta didik memiliki kategori sangat baik.